Desertification Problem in Western Rajasthan - Singh, Surendra; Kar, Amal; Joshi, D C; Kumar, Suresh; Sharma, K D (Annals of Arid Zone, 2016)
Desertification problem in western Rajasthan, as caused by accelerated and natural processes and manifested through degraded features like sand sheets, drifting sand, active dunes, deflation hollows, rills, gullies, soil crust, salt encrustations, impeded drainage conditions, poor vegetation cover, low plant density and low biomass production under different rainfall zones, has been highlighted in this paper. In the less than 300 mm rainfall zone, wind erosion/deposition, salinisation and waterlogging are the dominant processes of desertification. In the more than 300 mm rainfall zone, water erosion and wind deposition are the major processes leading to degradation of the croplands and grazing lands.